2004
DOI: 10.1002/bem.20051
|View full text |Cite
|
Sign up to set email alerts
|

On the thermal noise limit of cellular membranes

Abstract: Comparison of thermal noise limits and the effects of low frequency electromagnetic fields (LFEMF) on the cellular membrane have important implications for the study of bioelectro-magnetism in this regime. Over a decade ago, Weaver and Astumian developed a model to show that thermal noise can limit the efficacy of LFEMF. A recent report by Kaune [Kaune (2002) Bioelectromagnetics 23:622-628], however, contradicted their findings. Kaune assumes that the conductance noise current of cell membrane can be decompose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 24 publications
0
37
0
Order By: Relevance
“…It is pertinent to infer that exposure to magnetic fields induces quite a variety of biological effects. Different waveform magnetic field sources results in varied biological effects on living systems, as their frequency spectrums are diverse [39,58,59]. …”
Section: Discussionmentioning
confidence: 99%
“…It is pertinent to infer that exposure to magnetic fields induces quite a variety of biological effects. Different waveform magnetic field sources results in varied biological effects on living systems, as their frequency spectrums are diverse [39,58,59]. …”
Section: Discussionmentioning
confidence: 99%
“…In the ELF regime his noiseband vanished and thus allowed for the ''detection'' of typical power frequency fields by the cell membrane. Very recently, however, Vincze et al [2005] suggested revisions to Kaune's model. With these revisions the thermal noise power becomes larger and effectively white, that is, noise strength is independent of frequency.…”
Section: Introductionmentioning
confidence: 94%
“…With these revisions the thermal noise power becomes larger and effectively white, that is, noise strength is independent of frequency. In the model of Vincze et al [2005], ELF fields would once again be drowned out by thermal noise.…”
Section: Introductionmentioning
confidence: 98%
“…The proper selection uses the dipole relaxation of beta-dispersion connected to membrane-bound water [24]. This allows the zero-order electric-field action, which has no noise-induced thermal limit of the field [25]. The huge local dielectric permittivity of the transmembrane proteins and their clusters (rafts), are active in the electro-orientation of cells [26].…”
Section: Introductionmentioning
confidence: 99%